Dynamic principal component analysis with missing values. Issue 11 (17th August 2020) - Kwon, Junhyeon; Oh, Hee-Seok; Lim, Yaeji
Abstract : Dynamic principal component analysis (DPCA), also known as frequency domain principal component analysis, has been developed by Brillinger [ Time Series: Data Analysis and Theory, Vol. 36, SIAM, 1981] to decompose multivariate time-series data into a few principal component series. A primary advantage of DPCA is its capability of extracting essential components from the data by reflecting the serial dependence of them. It is also used to estimate the common component in a dynamic factor model, which is frequently used in econometrics. However, its beneficial property cannot be utilized when missing values are present, which should not be simply ignored when estimating the spectral density matrix in the DPCA procedure. Based on a novel combination of conventional DPCA and self-consistency concept, we propose a DPCA method when missing values are present. We demonstrate the advantage of the proposed method over some existing imputation methods through the Monte Carlo experiments and real data analysis.